Frequency of Extended-Spectrum Beta-Lactamase Producing Organisms Causing Urinary Tract Infection and Their Antibiotic Sensitivity Pattern - Rahman, Md Raziur; Rahim, Muhammad Abdur; Afroze, Samira Rahat; Poddar, Chinmay Shaha; Uddin, Khwaja Nazim (Journal of Medicine, 2017)
Background: The spectrum of bacteria causing urinary tract infection (UTI) and their antibiotic sensitivity pattern is not uniform. Escherichia coli and Klebsiella sp. are two common organisms responsible for UTI through-out the world. The incidence of UTI due to infection with extended-spectrum beta-lactamase (ESBL) producing organisms are increasing. This study was aimed to describe the frequency of ESBL positive organisms causing UTI and their antibiotic sensitivity pattern. Methods: This cross-sectional study was done in the Department of Internal Medicine, BIRDEM General Hospital from January to April, 2016. Results: Total number of patients was 137 with females predominance (M:F ratio 1 : 3.7). Mean age was 60.3 ±11.7 years. Most patients (131, 95.6%) of the study population were diabetic and glycaemic control was poor (mean HbA1c 9.3 ±2.3) in these subjects. Common symptoms were fever, vomiting, increased urinary frequency, dysuria, suprapubic pain, and loin pain. Neutrophilic leukocytosis was common (94.9%). E. coli (73.7%) was the commonest aetiological agent followed by Klebsiella (8.8%), Enterococcus (4.4%), Citrobacter (3.6%), Staphylococcus aureus (3.6%), Acinetobacter (2.9%), Enterobacter (1.5%), and Pseudomonas (1.5%). Over half of E. coli and of Klebsiella sp. and 100% of Enterobacter organisms were ESBL positive. Imipenem (100%), amikacin, netilmycin,and nitrofurantoin were among the most sensitive antibiotics. Conclusion: More than half (71, 51.82%) of UTI cases were due to ESBL positive organisms. Imipenem, amikacin, netilmycin, and nitrofurantoin remain the drug of choice. J MEDICINE January 2017; 18 (1) : 3-5